Procedure to categorize wheelchair cushion performance using compliant buttock models - Sprigle, Stephen; Deshpande, Yogesh (Frontiers in Bioengineering and Biotechnology, 2022)
Wheelchair cushion prescription often seeks to address tissue integrity in addition to other clinical indicators. Because hundreds of wheelchair cushion models are available, a benefit would result if cushions were classified in a more valid manner to help guide selection by clinicians and users. The objective of this research was to develop an approach to evaluate and classify wheelchair cushion performance with respect to pressure redistribution. Materials and Methods Two anatomically-based buttock models were designed consisting of an elastomeric shell that models overall buttock form and a rigid substructure that abstracts load-bearing aspects of the skeleton. Model shapes were based upon elliptical and trigonometric equations, respectively. Two performance parameters were defined, pressure magnitude and pressure redistribution. The pressure magnitude parameter compared internal pressure values of the test cushion to a flat foam reference material, resulting in three classifications, superior, comparable, and inferior. Surface sensors were used to distinguish cushions with high, moderate or low pressure redistribution performance. Ten wheelchair cushions were evaluated by both models using two loads that represent a range of body weights expected for 41-43 cm wide cushions. Results and Conclusions A classification matrix is proposed using both models and performance parameters. Two cushions met criteria for the highest level of performance, and one cushion was deemed to have inadequate performance for therapeutic value. The proposed method has a sensitivity to discern differences, compatibility with different sized cushions, and a versatility in classification. As such, it stands as an improvement over existing classification approaches.